Computational fluid dynamics models and congenital heart diseases - Pennati, Giancarlo; Corsini, Chiara; Hsia, Tain-Yen; Migliavacca, Francesco (Frontiers in Pediatrics, 2013)
Mathematical modelling is a powerful tool to investigate hemodynamics of the circulatory system. With improving imaging techniques and detailed clinical investigations, it is now possible to construct patient-specific models of reconstructive surgeries for the treatment of congenital heart diseases. These models can help clinicians to better understand the hemodynamic behaviour of different surgical options for a treated patient. This review outlines recent advances in mathematical modelling in congenital heart diseases, the discoveries and limitations these models present, and future directions that are on the horizon.